1990
DOI: 10.1002/path.1711610205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nucleolus organizer regions (NORs) by automatic image analysis: A contribution to standardization

Abstract: This study summarizes our experiences with the silver staining of nucleolus organizer regions (AgNORs) in a total of 580 tumours from ten different tissues. In contrast to other investigators, we made use of automatic image analysis for the evaluation of AgNORs. This provided good reproducibility as determined by the standard cumulative means technique and intra-observer (r1) and inter-observer (r2) agreement in 30 benign (r1 = 0.83-0.95, r2 = 0.76-0.92) and 50 malignant tissue samples (r1 = 0.72-0.85, r2 = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
0
2

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 11 publications
3
38
0
2
Order By: Relevance
“…In the present analysis the microscope was focused to find the maximum number of AgNORs visible at the same time. The number of nuclei counted was limited to 70 since the counting of AgNORs is time consuming and moreover the methodological studies have shown that the standard error of the mean does not vary significantly after 50-60 nuclei has been counted (Rushoff et al, 1990b). In the present analysis the intraobserver variation of the mean was 5 x % which is comparable to results observed by other researchers (Mansour et al, 1990;Rushoff et al, 1990b;Sivridis & Sims, 1990).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In the present analysis the microscope was focused to find the maximum number of AgNORs visible at the same time. The number of nuclei counted was limited to 70 since the counting of AgNORs is time consuming and moreover the methodological studies have shown that the standard error of the mean does not vary significantly after 50-60 nuclei has been counted (Rushoff et al, 1990b). In the present analysis the intraobserver variation of the mean was 5 x % which is comparable to results observed by other researchers (Mansour et al, 1990;Rushoff et al, 1990b;Sivridis & Sims, 1990).…”
Section: Discussionsupporting
confidence: 83%
“…It is hard to imagine the use of AgNORs alone in predicting individual cases of bladder cancer due to considerable overlap in AgNOR counts between malignant and more benign bladder tumours. The results encourage for further studies giving special emphasis to standardisation of measurement process and this refers to morphometric methods, in particular (Rushoff et al, 1990a;Rushoff et al, 1990b).…”
Section: Discussionmentioning
confidence: 80%
“…23 A further factor influencing the result, apart from the lymphoma grade, is the protocol used for the AgNOR stain, especially the incubation time of the silver nitrate solution. 8,9 Although in our study, the incubation period was 12 minutes, according to the proposals of the International Committee on AgNOR Quantitation, 14,15 the silver nitrate solution was applied for 30 minutes 4 and 45 minutes 4 in the other studies. Therefore, it can be hypothesized that our results would have been even higher in case of a longer incubation period and thus not comparable with the previously published data.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, manual counting of AgNORs by eye is subjective in human specimen, especially when the silver-stained dots overlap, 12,13 whereas automatic image analysis provided good reproducibility. 9 For this reason, guidelines for standardization were made by the ''International Committee on AgNOR Quantitation'' to provide reproducible data among the different laboratories that assess proliferation in human biopsy specimens and FNAs. 14,15 To our knowledge, a standardized protocol has not been used in veterinary medicine for AgNOR staining of a cytologic specimen.…”
mentioning
confidence: 99%
“…To test the hypothesis of ras transformation being associated with a more intense nucleolar activity in human breast epithelial cells in vitro, we examined the AgNOR staining profile (Rueschoff et al, 1990;Derenzini and Ploton, 1991;Vidal et al, 1994) of MCF-10A cells transfected with the c-Ha-ras oncogene in comparison with that of nontransformed MCF-10A cells.…”
Section: Introductionmentioning
confidence: 99%